Subliminal Messages in Bintang Beer Advertisements: a Semiotic Study - Desak Putu Eka Pratiwi; I Komang Sulatra; I Gede Suardana (Universitas Nahdlatul Wathan Mataram, 2022)
Advertising is a form of communication for marketing and is used to encourage and persuade people to take an action. As well as news, advertisements are also used to convey messages. This study aims to analyze verbal and visual signs in Bintang beer advertisements in order to discover the subliminal messages delivered by the company. The data were taken from three selected Bintang beer advertisements. They are Bintang Pilsener, Bintang Zero 0.0% and Bintang Radler. This study used observation method and note-taking technique in collecting the data. The data were analyzed by descriptive qualitative method using theory of Semiotics proposed by Barthes (1998). By conducting this study, it is found that there are interesting unseen messages in Bintang beer advertisements. The finding shows that both verbal and visual signs play crucial roles in presenting meaningful and interesting advertisement to succesfully deliver messages to the target consumers. Keywords: advertisement, sign, meaning, verbal, visual